Food Certification Through Catfish Crackers as an Effort to Increase Food and Economic Security in BUMDes Gesang Sejahtera, Gesang Village, Tempeh District, Lumajang Regency. - Istikomah, Istikomah; Hasanah, Miftahul (Mujtama Jurnal Pengabdian Masyarakat, 2023)
BUMDes is basically an instrument for social and commercial-based local economic empowerment institutions that have a strong focus on the interests and progress of village communities. One of the superior business units in BUMDes Gesang Sejahtera is catfish cultivation. Catfish cultivation business units are in great demand among local village communities, because apart from the affordable price, catfish also have delicious meat and high nutritional value. The management of BUMDes Gesang Sejahtera has tried an innovation from catfish products to catfish nuggets. Along the way, catfish nuggets are less popular with the public because they are easily spoiled and the production price is high. The aim of this service activity is to find an innovative form of catfish product that is durable and has value for sale. The method used in this service activity is PRA (Participatory Rural Appraisal). The result of this activity was the creation of an innovation in catfish crackers and a halal certificate.